Dance as a complementary pedagogic tool in architectural education - Daskalakos, C. (South African Journal of Higher Education, 2021)
Architectural education is complex as it requires the development of both objective and subjective knowledge. While explicit knowledge that meets the trends in universities to create value by preparing students for industry, are easier to include in a curriculum, implicit knowledge based on personal experience that facilitates flexibility and creativity is more challenging. An example in the training of future architects is highlighted by the tendency to rely heavily on the visual sense in relation to buildings, which tends to objectify them, thereby ignoring their experiential components. The move towards digital applications in design further alienates the designers from this experiential aspect, as the technology leads to disembodiment and hence the sensitivity to subjective aspects of design. Design of space is influenced subconsciously by habitual patterns of behaviour embedded culturally and autobiographically in body memory. Dance as a complementary pedagogic tool can develop understanding of self and the body, bringing such habitual patterns into awareness. In addition to creating awareness, dance offers the tools to explore alternatives, creating a new meaning and relationship to space thus aiding the design skills of students. A curriculum that includes the subjective and autobiographical aspects of the student reflects the educational theory of Currere proposed by William Pinar and a pedagogic approach that reflects the theories of Georgio Agamben’s “rhythm” and Alfred Whitehead’s “cycles in learning”.